Effect of Paracetamol on Sperm Biological Parameters and Testosterone Level in Albino Male Mice - Habiba Eljaafari; Zainab EL Mabrouk; Marwan Rashrash (Khalij-Libya Journal of Dental and Medical Research, 2021)
Backgrounds and objectives. The wide use of paracetamol at high doses was found to alter sperm parameters especially sperm morphology, and thus its fertilizing capability. Therefore, the present study was designed to use different doses of paracetamol to identify its effect on sperm parameters and testosterone levels in adult male mice. Methods. Forty adult male albino mice were divided into four equal groups, the first group injected with distilled water, the three treated groups injected with different doses of paracetamol (20, 40, 80 mg/kg body weight /day) over a period of 42 days. All doses were given once daily via intraperitoneal injection. Results. The results showed that paracetamol causes a significant decrease in body weight, non-significance effect on sperm parameters at doses of 20 and 40 mg/kg, while it led to a significant effect on sperm parameters at a dose of 80 mg/kg. Also, there was no difference in testosterone level between control and the treated groups (20 and 40mg/kg). But it showed a significant decrease in testosterone level at dose 80 mg/kg treated groups. Conclusion. It is considered safe to use paracetamol at doses 20 and 40 mg/kg but the dose 80 mg/kg has adverse effects on sperm parameters and testosterone level.